CURRENT STATE OF NATIONAL LEGISLATION OF UKRAINE IN RESPECT TO OF PERSONAL DATA PROTECTION AND ITS ADAPTATION TO THE NORMS AND STANDARDS OF EU LAW - Kozyrieva, Valentyna P.; Zhabiak Аndriana A. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2017)
The article provides with the characteristics of current state of national legislation of Ukraine in respect to data protection and its adaptation to the norms and standards of EU law. The author investigates the problematic issues of personal data protection on the basis of current operating legislative norms and outlines the main ways of its adaptation to the norms and standards of EU law.